Pendidikan Ideal Dalam Perspektif Buya Hamka : Integrasi Ranah, Spritual, Intelektual, Dan Moral - Muhajir Darwis; Nila Hanifa; Siti Aisyah; Abid El Razin; Syiren Julia Asmarani; Nur’ain Syafrina (Universitas Pakuan, 2026)
Ideal Education in the Perspective of Buya Hamka: Integration of the Realm, Spiritual, Intellectual, and Moral This study aims to examine the concept of the ideal educator according to Buya Hamka and to analyze the spiritual, intellectual, and moral dimensions that constitute the essential characteristics of an educator in his educational thought. Buya Hamka viewed educators not merely as transmitters of knowledge but also as spiritual guides, moral role models, and character builders for students. This research employs a qualitative approach through library research by analyzing Hamka’s educational ideas and relevant literature. The findings reveal that the ideal educator, according to Buya Hamka, must possess a balanced integration of spirituality, intellectual competence, and moral integrity. In the spiritual dimension, educators are expected to demonstrate sincerity, piety, and dedication, viewing their profession as an act of worship to Allah. In the intellectual dimension, educators should master knowledge, think critically, and integrate religious and general sciences. In the moral dimension, educators must exemplify honesty, responsibility, discipline, and noble character in their daily lives. Amid contemporary challenges such as globalization, materialism, and moral decline, Buya Hamka’s concept of the ideal educator remains highly relevant and applicable to modern education. His educational philosophy offers a holistic framework that harmonizes spiritual, intellectual, and moral development in shaping students’ character and personality.